A stratified bootstrapping approach to assessing the success of TQM implementation in Peruvian companies. (2nd January 2022) - Benzaquen, Jorge; Charles, Vincent
Abstract : Total Quality Management represents a management approach to long-term success used by organisations worldwide to improve their products and processes and achieve customer satisfaction, being perceived as a source of competitive advantage. A look at the existent literature points towards a lack of studies dedicated to examining TQM implementation in developing countries, especially in Latin America and particularly in Peru. The current industrial needs in Peru, however, require further research on this topic because a larger number of organisations choose nowadays to obtain quality certifications to improve their products. In this context, the objective of the present paper is to provide a snapshot of the current state of TQM implementation in Peru, aiming to identify which key quality factors are the most and least developed for successful TQM implementation. To this aim, the present paper uses a bootstrapping approach, within the framework of a nine-factor model of TQM in business. The study is performed on a sample of 4, 668 Peruvian companies, across 52 industry sectors. Findings reveal that the most developed key quality factors in the companies surveyed are: Top Management, Quality Planning, Quality Audit and Assessment, Education and Training, and Process Control and Improvement. Implications for practice are provided.